Ex-regular users of public transport: their reasons for leaving and returning - Vicente, P.; Reis, E. (Journal of Public Transportation, 2018)
This paper describes the characteristics of former regular users of public transport in the metropolitan area of Lisbon. It also examines why these people stopped using public transport and explores what would make them become regular users again. The empirical results revealed significant socio-demographic differences between current and ex-regular users, namely in relation to gender and social level. Differences were also found in travel characteristics, car ownership, and satisfaction with the transit service. The main reasons given by ex-regular users for no longer using public transport included changes in their lives (e.g., change in workplace/residence/ school or becoming unemployed) and the availability of alternative transport (e.g., company car). Although the likelihood of becoming a regular user again was very low (27%), the strongest potential motive for doing so was a change in workplace/residence/school. Based on the study’s empirical results, managerial implications for the public transport service are addressed in the conclusion.